157k views
5 votes
6(2x + 2) = 10 - 4x​

User Shanei
by
5.6k points

2 Answers

4 votes

Answer:

-0.125

Explanation:

6(2x+2)=10-4x

12x+12=10-4x

16x+12=10

16x=-2

16x/16=-2/16

x=-0.125

User Jiang Bian
by
5.6k points
5 votes

Answer:

x = -1/8

Explanation:

6(2x + 2) = 10 - 4x​

Distribute across brackets

12x + 12 = 10 - 4x

Combine like terms over both sides

16x = -2

x = -2/16 <=reduce

x = -1/8

User Abhishek AN
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.